2017
DOI: 10.1097/md.0000000000008658
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent spinal primitive neuroectodermal tumor with brain and bone metastases

Abstract: Rationale:Primary spinal primitive neuroectodermal tumor (PNET) is relatively rare in all age groups, and the prognosis in most cases of spinal PNETs appears to be poor, with a median patient survival of 1 to 2 years. We present a case with recurrent spinal PNET with brain and bone metastases that was successfully treated by multimodality treatment.Patient concerns:A 14-year-old teenage girl had suffered from progressive left upper back pain with bilateral lower legs weakness and numbness for 1 year. After tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…According to our results, pPNETs can metastasize to distant sites like the brain, bone, lungs, lymph nodes, and liver, 14 which is consistent with reported cases. 15,16 As such, preoperative whole-body CT and/or MRI is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our results, pPNETs can metastasize to distant sites like the brain, bone, lungs, lymph nodes, and liver, 14 which is consistent with reported cases. 15,16 As such, preoperative whole-body CT and/or MRI is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 16 reported that a 14-year-old girl survived >7 years after being diagnosed with pPNET, with no recurrence in >4 years. The patient underwent craniospinal radiotherapy and chemotherapy after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although PNET is the second most common malignant neoplasm in childhood, the spinal cord as the primary site is extremely rare in all age groups [1][2][3]. According to the study of Amirjanshidi et al, there aer only 29 cases reported in 22 studies in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Primary spinal PNETs are more prevalent in pediatric populations and young adults, with a median age at diagnosis around 24 years-old, and are more commonly seen in males than in females, with a prevalence of approximately 2:1 [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation